The Relationship of burnout to nurse job satisfaction at Semen Gresik Hospital - Al Fanani, Tamam; Paskarini, Indriati (Jurnal Keperawatan, 2023)
Introduction: The nursing profession is a professional and technical profession that is distinguished by the combination of mental and physical labor and the high risk of work. A nurse can feel work exhaustion or usually called burnout and affects job satisfaction   Objectives:  The purpose of this study was to analyze the relationship between burnout and job satisfaction among nurses. Methods: The research design used was descriptive statistical and correlational analysis with a cross-sectional approach. A total sample of 115 nurses who met the inclusion criteria was selected using the simple random sampling technique. Data were analyzed using Spearman's rank with α = 0.05. Results: The results showed that the majority of participants were at a moderate level of burnout (n = 93, 89%). The study also found that the majority of participants have an ambivalence level toward job satisfaction (n = 54, 47.0%), and burnout has a negative correlation with job satisfaction (p = 0.000 with a correlation value of -0.483). Conclusions: The level of burnout was correlated with job satisfaction. therefore it is necessary to reduce burnout levels so that nurse job satisfaction increases and can improve nurse performance.